Perceptions of Public Officers Towards the Effects of Climate Change on Ecosystem Services: A Case-Study From Northern Portugal - Vaz, Ana Sofia; Graça, Marisa; Carvalho-Santos, Cláudia; Pinto, Eva; Vicente, Joana R.; Honrado, João P.; Santos, João A. (Frontiers in Ecology and Evolution, 2021)
How institutional stakeholders perceive the supply and demand of ecosystem services (ES) under distinct contexts determines which planning actions are deemed priority or not. Public officers play a crucial role in social-ecological management and decision-making processes, but there is a paucity of research exploring their perceptions on ES supply and demand under a changing climate. We address this gap through an exploratory study that analyses the views of public officers on the potential impacts of climate-change related drivers on multiple ES in a major administrative region from Portugal (EU NUTS 3). We combined qualitative spatial data from participatory maps and semi-quantitative answers from questionnaire-based surveys with 22 officers from public institutions contributing to territorial planning. Contrary to other similar studies, public officers shared a common view on the importance of ES. This view aligns with scientific projections on how a changing climate is expected to influence ES in the region over the next decade. In agreement with other observations in Mediterranean regions, the most perceivably valued ES concerned tangible socio-economic benefits (e.g. periurban agriculture and wine production). Surprisingly, despite the region’s potential for cultural ES, and considering the impacts that climate change may hold on them, recreation and tourism did not seem to be embedded in the officers’ views. We explore the implications of our findings for territorial planning and social-ecological adaptation, considering that the way stakeholders manage the territory in response to climate change depends on the extent to which they are aware and expect to experience climatic consequences in the future.